Sosialisasi Pengolahan Limbah Medis Di RSUD Gambiran Kota Kediri - Yuly Peristiowati (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: Medical waste is a waste product from a medical activity. Medical waste must be treated as soon as possible after it is generated. Improper processing of medical waste will increase the source of infection and can lead to the risk of nosocomial infection. Data from the sanitarian section of Gambiran Kediri Hospital said that in 1 day on average 190 kg of medical waste was produced, including injection equipment, ampoules, infusion bottles, infusion hoses, catheters, used injection bottles, gloves, masks, cotton wool, plaster, medicine packs. , gauze and bandages, produced by 20 wards. Methods: Community Service activities carried out are providing socialization to all employees and patients at the Gambiran Hospital, Kediri City in the form of counseling on how to process Medical Waste starting from the initial disposal site in the room to the TPS B3 section (B3 Waste Disposal Place using the leaflet method, and electronic media at the hospital. Results: The result of this community service activity was that problems related to medical waste processing were still mixed with medical waste and non-mediated waste in several rooms, the color of the plastic bags used did not match the SOP, the time used for distributing clean linen is not in accordance with the SOP. Conclusion: After community service was carried out at Gambiran Hospital, Kediri City, we encountered various problems including gaps between targets and achievements. Using the data we had obtained, we processed the data by determining priority problems based on USG ( Usgensi Seriousness Growth), based on the results of the problem priority analysis we determine the SWOT analysis, determine the intervention and then carry out the implementation according to the problems that are found correctly.